Study on the ITO/ZnO interface and its effect on CdS/CdTe solar cell performance (Superficies y Vacío, 2016)
ZnO thin films have been deposited on ITO coated glass substrates, using RF magnetron reactive sputtering from a Zn target. The ZnO films were annealed at 560 °C for 1 hour, in order to promote the diffusion of the ITO into ZnO. The properties of the samples were analyzed by X- ray diffraction (XRD), UV-Vis spectroscopy and X-ray photoelectron spectroscopy (XPS). The ITO/ZnO interface showed a diffusion of 50 nm approximately. In order to study the effect of ZnO thickness, in the performance of the CdS/CdTe solar cell, we used an AMPS-1D solar simulator; the results showed that reduction of the ZnO thickness had a weak influence in the efficiency of the solar cell.